Screening of medium components for glucose oxidase production by Aspergillus terreus UniMAP AA-1 - Ahmad Anas, Nagoor Gunny; Arbain, Dachyar, Dr.; Muhammad Syarhabil, Ahmad, Dr.; Mohamad Fahrurrazi, Tompang (IACSIT Press, Singapoore, 2012)
Link to publisher's homepage at www.iacsit.org/